UTILIZATION OF THE YARD THROUGH VEGETABLE PLANTING PRACTICES INTEGRATED MATHEMATICS FOR STUDENTS AT ADIWIYATA SCHOOL - Ai Tusi Fatimah; Asep Amam; Adang Effendi (LPM Universitas Pasundan, 2022)
Utilization of yards at MI Hadapherang to improve the quality of Adiwiyata schools, support active student participation, management of environmentally friendly facilities, and the application of an environment-based curriculum in mathematics learning. The utilization of the yard by planting vegetables by students. The activity stages consist of preparation, implementation, and evaluation. The preparation stage is the provision of tools and materials, worksheets, and evaluation instruments. The implementation stage is the socialization of the practice of planting vegetables in the schoolyard and mathematics, followed by the planting vegetable practice from seedling to harvesting. The evaluation stage saw planting vegetable practice and students' mathematical understanding abilities. The implementation method is interactive question and answer and practice/experiment. The result of this activity is the increase in students' knowledge, understanding, and experience about the practice of growing vegetables and the integration of mathematics in the practice of planting vegetables. Active participation of students in vegetable planting activities in the high category. The students' mathematical instrumental understanding is high while the relational understanding is middle. The results of student activities become a means of supporting greenhouses in the schoolyard.